Characterization of the Neuroendocrine Tumor Immune Microenvironment. Issue 9 (October 2018) - da Silva, Annacarolina; Bowden, Michaela; Zhang, Sui; Masugi, Yohei; Thorner, Aaron R.; Herbert, Zachary T.; Zhou, Chensheng Willa; Brais, Lauren; Chan, Jennifer A.; Hodi, F. Stephen; Rodig, Scott; Ogino, Shuji; et al.
Abstract : Objectives: The immune environment and the potential for neuroendocrine tumors (NETs) to respond to immune checkpoint inhibitors remain largely unexplored. We assessed immune checkpoint marker expression, lymphocytic infiltrate, and associated mutational profiles in a cohort of small intestine and pancreatic NETs. Methods: We assessed expression of PDCD1 (PD-1), CD274 (PD-L1), and PDCD1LG2 (PD-L2) in archival tissue from 64 small intestine (SINETs) and 31 pancreatic NETs (pNET). We additionally assessed T-cell infiltrates, categorizing T-cell subsets based on expression of the T-cell markers CD3, CD8, CD45RO (PTPRC), or FOXP3. Finally, we explored associations between immune checkpoint marker expression, lymphocytic infiltrate, and tumor mutational profiles. Results: Expression of PD-1 or PD-L1 in small intestine or pancreatic NET was rare, whereas expression of PD-L2 was common in both NET subtypes. T-cell infiltrates were more abundant in pNET than in SINET. We found no clear associations between immune checkpoint marker expression, immune infiltrates, and specific mutational profile within each tumor type. Conclusions: Our findings provide an initial assessment of the immune environment of well-differentiated NETs. Further studies to define the immunologic differences between pNET and SINET, as well as the role of PD-L2 in these tumors, are warranted.